CONTRASTIVE ANALYSIS OF CHINESE AND INDONESIAN EXCLAMATIVE SENTENCES IN WEBTOON TITLED《女神降临》NǙSHÉN JIÀNGLÍN/THE SECRET OF ANGEL - Ariqah, Nisa Faiqatul (Bambuti, 2024)
Abstract. This research is entitled, "Contrastive Analysis of Chinese and Indonesian Exclamative Sentences in Webtoon titled《女神降临》Nǚshén Jiànglín/The Secret of Angel". In this research about the structure and meaning of Chinese and Indonesian exclamative sentences are compared in terms of similarities and differences. The purpose of this research is to analyze the similarities and differences in the structure of the form and meaning of the exclamative sentences contained in the Chinese and Indonesian Webtoon entitled《女神降临》Nǚshén Jiànglín/The Secret of Angel by using the theory of contrastive analysis as the main method and descriptive analysis as the supporting method.Contrastive analysis theory to analyze data comparing two different languages, namely Indonesian and Mandarin and descriptive analysis theory to systematically describe the meaning of a word, phrase, or sentence which is then grouped according to certain structural patterns. The results of the analysis show that the form and structure of exclamative sentences in Indonesian and Chinese webtoons have similarities and differences because the structure and form of exclamative sentences in Chinese webtoons are influenced by the elements of their formation is particles and interjections. Keywords: Contrastive Analysis; Exclamative Sentences; Webtoon. Abstract (In Bahasa). Penelitian ini berjudul, “Analisis Kontrastif Kalimat Eksklamatif Bahasa Mandarin dan Bahasa Indonesia dalam Webtoon berjudul 《女神降临》 Nǚshén Jiànglín /The Secret of Angel”. Dalam penelitian ini, bentuk struktur dan makna pada kalimat eksklamatif dalam bahasa Mandarin dan Indonesia memiliki perbandingan persamaan dan perbedaannya. Tujuan penelitian ini adalah menganalisis persamaan dan perbedaannya struktur bentuk dan makna kalimat eksklamatif yang terdapat dalam Webtoon bahasa Mandarin dan bahasa Indonesia yang berjudul 《女神降临》 Nǚshén Jiànglín (The Secret of Angel) dengan menggunakan teori analisis kontrastif sebagai metode utama dan analisis deskriptif sebagai metode pendukung. Teori analisis kontrastif untuk menganalisis data membandingkan dua bahasa yang berbeda, yaitu Indonesia dan Mandarin dan teori analisis deskriptif untuk menggambarkan secara sistematis makna dari suatu kata, frase, ataupun kalimat yang kemudian dikelompokkan menurut pola struktur tertentu. Hasil analisis menunjukkan bahwa bentuk dan struktur kalimat eksklamatif dalam webtoon bahasa Indonesia dan Mandarin memiliki persamaan dan perbedaan karena struktur dan bentuk kalimat eksklamatif dalam webtoon bahasa Mandarin dipengaruhi oleh unsur pembentukannya, yaitu partikel dan interjeksi. Kata kunci : Analisis Kontrastif, Kalimat Eksklamatif, Webtoon.